2013
DOI: 10.1002/pds.3479
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a population‐based method to assess drug‐induced alterations in the QT interval: a self‐controlled crossover study

Abstract: QT prolonging effects were common and varied in strength. Our results lend support to past Food and Drug Administration regulatory actions and support the role for ongoing surveillance of drug-induced QT prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 72 publications
3
16
0
Order By: Relevance
“…However, in a recently controlled crossover study for 90 drugs with 59,467 subjects (42) aripiprazole showed a mean QTc prolongation of 7.6 ms, that is similar to our data. In addition, Torsade de Pointes (a form of ventricular tachycardia) was reported in a patient without history of cardiovascular risk after administration of 2.5 mg of aripiprazole (43).…”
Section: Pharmacodynamicssupporting
confidence: 82%
“…However, in a recently controlled crossover study for 90 drugs with 59,467 subjects (42) aripiprazole showed a mean QTc prolongation of 7.6 ms, that is similar to our data. In addition, Torsade de Pointes (a form of ventricular tachycardia) was reported in a patient without history of cardiovascular risk after administration of 2.5 mg of aripiprazole (43).…”
Section: Pharmacodynamicssupporting
confidence: 82%
“…From the heat maps in Fig 3, it is evident that compounds with half-lives greater than 1 hour (especially compounds with half-lives between 12 and 24 hours) are enriched in this KEGG pathway. The serotonergic synapse pathway ( hsa04726 ) is affected by trimipramine, an important antihistamine and sedative with an exact half-life of 23–24 hours [97, 98]. Fig 3 also shows that compounds with half-lives between 12 and 24 hours are enriched in this KEGG pathway, which supports the accuracy and efficacy of our prediction.…”
Section: Resultssupporting
confidence: 69%
“…The data from a large number (n = 2005) of users in a clinic setting found that venlafaxine use was associated with a significantly increase in QTc. 31 The probability of a person having a dangerously prolonged QTc is greater in women and older person. The ability of venlafaxine to increase QTc is supported by cases of patients with markedly prolonged QT with venlafaxine treatment, 62 and with venlafaxine overdose.…”
Section: Venlafaxinementioning
confidence: 99%
“…30 In the Kaiser Permanente Medical Care Program of Northern California, there were significant increases in QTc for HPD, thioridazine, imipramine, citalopram, venlafaxine, clozapine, ziprasidone, sertraline quetiapine, nortriptyline, and risperidone. 31 In a meta-analysis, using a Bayesian-framework with both direct and indirect comparisons of randomized controlled trials comparing 15 antipsychotics and placebo in the acute treatment of schizophrenia, Leucht et al 32 found that most antipsychotics were associated with an increase in QTc. However, there are considerable differences in the magnitude of the increase in QTc between drugs.…”
Section: Psychotropics and Qtc Prolongationmentioning
confidence: 99%